دراسة مقارنة بين الارتباط التقويمي و التقويمي الحصين : مع جانب تطبيقي - ذكاء يوسف عزيز (PROSPECTIVE RESEARCHES, 2023)
The research aims at comparison between the canonical correlation and robust canonical by using robust estimate for covariance matrix (minimum covariance determinant estimators) in the style of the robust canonical correlation. These two styles are the statistical methods that are unfamiliar in dealing with the statistical data. Most of the researches depend on the style of a study of a group of independent variables with one dependant variable, but sometimes the researcher is concerned with the relations among a group of dependent variables and a group of independent variables. The research studies the relation between some of the knowledge managerial processes and managerial administrative corruption. For the purpose of the comparison between the two styles to determine the efficiency of the estimate, the researcher uses a scale of the mean square error. The results of the analysis indicate that the robust canonical correlation is better than the usual canonical correlation.